KDD for Business Intelligence - Khan, Rafi Ahmad (Journal of Knowledge Management Practice, 2012)
Emergence of knowledge based economy has posed serious challenges to companies. Intelligent organizations recognize that knowledge is an intellectual asset that grow over time and when harnessed effectively, can sustain competition and innovation. Organizations can use IT for leveraging the entire organization’s intellectual resources for great financial impact. Business Intelligence (BI) along with KDD (Knowledge Discovery in Databases) plays a pivotal role in leveraging the intellectual assets of companies by creating, storing and sharing that knowledge for effective decision making. Companies are now realizing the potential payoffs of KDD applications along with BI. Consequently, BI is spreading its wings to cover small, medium and large companies. This paper explores the concepts of BI, KDD, process of knowledge discovery, key levers of knowledge strategy and benefits of BI.